PUTUSAN HAKIM DALAM MENJATUHKAN SANKSI PIDANA PENJARA KEPADA ANAK PELAKU TINDAK PIDANA PENGANIAYAAN (Putusan Nomor: 3/Pid.Sus-Anak/2020/PN-Enr) - Charista Eforina Waruwu; Itok Dwi Kurniawan (Verstek, 2023)
This article aims to determine the suitability of the judge's decision in imposing prison sentences on children who are perpetrators of abuse based on the provisions of Article 354 Paragraph (2) of the Criminal Code and the Law on the Juvenile Criminal Justice System. The type of research used is normative legal research which is prescriptive and applied. This legal research approach is a case approach. The legal materials used consist of primary legal materials and secondary legal materials. The technique of collecting legal materials used is literature study. The technique of analyzing legal materials used in writing this law is the syllogism method using deductive thinking patterns. The results of this study indicate that the judge's decision in the Enrekang District Court Decision Number 3/Pid.sus-Anak/2020/PN-Enr has given a decision that is not in accordance with the provisions contained in Article 79 Paragraph (2) of the Child Criminal Protection System Act. because the Judge did not give consideration that refers to Article 354 of the Criminal Code.Keywords: Judge's Decision, Persecution, Child Defendant